Pengaruh Pemberian Terapi Guided Imagery terhadap Perubahan Intensitas Nyeri Ibu Bersalin Post Sectio Caesarea di Rumah Sakit Bersalin Di Kota Padang - Silfina Indriani; Ika Yulia Darma (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The trend of delivery by caesarean sectio (SC) in Indonesia increased by 10% from 7% in the 2007 IDHS to 17% in the 2017 IDHS. Pain is an inconvenience that is often experienced by women giving birth after caesarean sectio. Complementary pain management can be done with guided imagery therapy. The purpose of this study was to determine the effect of giving guided imagery therapy to changes in the intensity of pain in post-sectio caesarean delivery mothers at a maternity hospital in the city of Padang in 2021.This type of research is quasi-experimental with a one group pretest posttest design. The research population was post-sectio caesarean delivery mothers with a total sample of 30 people, sampling using purposive sampling technique. Data were analyzed univariately and bivariately using paired sample t-test. The results showed that the average maternal pain intensity before intervention was 6.90 and after guided imagery therapy the average pain intensity was 3.70 with a mean difference of 3.20. The results of statistical tests showed that there was an effect of giving guided imagery therapy to changes in the intensity of pain in postpartum mothers with caesarean sectio with a p value of 0.000 (p value <0.05). There is a significant effect between the pain intensity of post-cesarean delivery mothers before and after being given guided imagery therapy. It is hoped that this therapy can be implemented in the management of pain experienced by mothers after caesarean sectio.